View the step-by-step solution to:

Question

Solve example : y =

e3x , and y = e2x-1

Top Answer

Please see the attached... View the full answer

IMG_5775.jpg

y = e y = e 2x - 1
Equating egl and eq 2
0 52 - p 2 2 - 1
Taking natural log on both sides
un e 32
( ine= 1 ?
32 = 22-1
n = =1
n = -1
y = e
3 ( -1 )
= 0 - 3
y = e- 3

Sign up to view the full answer

Why Join Course Hero?

Course Hero has all the homework and study help you need to succeed! We’ve got course-specific notes, study guides, and practice tests along with expert tutors.

  • -

    Study Documents

    Find the best study resources around, tagged to your specific courses. Share your own to gain free Course Hero access.

    Browse Documents
  • -

    Question & Answers

    Get one-on-one homework help from our expert tutors—available online 24/7. Ask your own questions or browse existing Q&A threads. Satisfaction guaranteed!

    Ask a Question